Finite Element Analysis of Magnetic Saturation of Disk-type Magnetorheological Brake - Qiao Zhen; Huang Jin (Jixie chuandong)
An evaluation magnetic saturation rate is proposed due to magnetic saturation degree not clear in the magnetorheological device. The magnetic field finite element analysis of disc- type magnetorheological brake is carried out,and the simulation results are analyzed by magnetic saturation evaluation function. The results indicate that,the brake just happens to be magnetic saturation during the input current is 2 A. The structure of brake is optimized by magnetic saturation analysis and brake in before and after the optimization is analyzed by magnetic saturation evaluation function and magnetic saturation evaluation rate,the results indicate that,brake torque increased by 57%,the evaluation of magnetic saturation rate decreased by 0. 95%. Furthermore,the magnetic fields in the three types of magnetorheological brake are analyzed by using finite element in the case of equal of magneto motive force,the results indicate that,the side- wall- type brake and the excitation coil is the opposite winding of the resistance magnetic saturation capacity is the strongest,the outer- type brake of resistance magnetic saturation capacity is the weakest. The outer- type brake of working gap magnetic induction intensity distribution is more uniform,while the side- wall- type brake of working gap magnetic induction intensity distribution is uneven extremely. The working gap magnetic induction intensity distribution of the same- direction- winding is relatively even than the opposite- direction- winding in the side- wall- type brake.